2014
DOI: 10.1111/head.12300
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Family Psychiatric and Headache History on Migraine‐Related Health Care Utilization

Abstract: Family history of anxiety, but not depression, was associated with utilizing non-pharmacologic treatments for headache. Also, disability was associated with utilizing non-pharmacologic treatments for headache. However, participants reported low rates of utilization for non-pharmacologic treatments with grade-A evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…The prevalence of chiropractic use for those with migraine ranged from 1.0 to 36.2% (mean: 14.4%) within the general population [1921, 4852] and from 8.9 to 27.1% (mean: 18.0%) within headache-clinic patient populations [53, 54]. The prevalence of chiropractic use for those reported as headache ranged from 4 to 28.0% (mean: 12.9%) within the general population [20, 48, 51, 5557]; ranged from 12.0 to 22.0% (mean: 18.6%) within headache/pain clinic patient populations [5860] and from 1.9 to 45.5% (mean: 9.8%) within chiropractic patient populations [61–69].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of chiropractic use for those with migraine ranged from 1.0 to 36.2% (mean: 14.4%) within the general population [1921, 4852] and from 8.9 to 27.1% (mean: 18.0%) within headache-clinic patient populations [53, 54]. The prevalence of chiropractic use for those reported as headache ranged from 4 to 28.0% (mean: 12.9%) within the general population [20, 48, 51, 5557]; ranged from 12.0 to 22.0% (mean: 18.6%) within headache/pain clinic patient populations [5860] and from 1.9 to 45.5% (mean: 9.8%) within chiropractic patient populations [61–69].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence use of physiotherapy for those with migraine ranged from 9.0 to 57.0% (mean: 24.7%) within the general population [19, 20, 48, 52] and from 4.9 to 18.7% (mean: 11.8%) within headache-clinic patient populations [54, 70]. The prevalence use of physiotherapy for those reported as headache ranged from 12.2 to 52.0% (mean: 32.1%) within the general population [20, 48] and from 27.8 to 35.0%% (mean: 31.4%) within headache/pain clinic populations [60, 70].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study found that a family history of anxiety was associated with self-reported usage of non-pharmacological treatments for headache. However, most of the participants in non-pharmacological treatments who reported such use, were not those with grade A evidence 27. Controlling anxiety of patients with migraine is associated with improved quality of life, adherence to a migraine treatment plan, and effectiveness of migraine treatment 22…”
Section: Psychiatric Comorbidities Associated With Migrainementioning
confidence: 99%